2022
DOI: 10.3390/polym14061183
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared-Light-Assisted Self-Healing Graphene-Thermopolyurethane Composite Films

Abstract: Graphene-thermopolyurethane (G-TPU) composite films were fabricated and the effects of the TPU initial concentration, characteristics of TPU, and graphene loading on the electrical, mechanical, thermal, infrared thermal response and near-infrared-light-assisted self-healing properties of the composite films were investigated in detail. The experimental results demonstrate that the comprehensive performances of the composite film are related to the initial concentration of the TPU solution and the characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Especially for the system containing photothermal fillers (for example, carbon nanotubes and graphene), NIR light could be converted into heat more efficiently. 21–23 Bonardi et al 24 reported the photothermal induced free radical polymerization of (meth)acrylates using graphene as well as carbon nanotubes as NIR light heaters. After 100 s irradiation of NIR light, the system temperature reached more than 100 °C which induced the polymerization of the monomer, and the final double bond conversion rate reached 75%.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for the system containing photothermal fillers (for example, carbon nanotubes and graphene), NIR light could be converted into heat more efficiently. 21–23 Bonardi et al 24 reported the photothermal induced free radical polymerization of (meth)acrylates using graphene as well as carbon nanotubes as NIR light heaters. After 100 s irradiation of NIR light, the system temperature reached more than 100 °C which induced the polymerization of the monomer, and the final double bond conversion rate reached 75%.…”
Section: Introductionmentioning
confidence: 99%